1982
DOI: 10.1172/jci110548
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular activation of complement and acute lung injury. Dependency on neutrophils and toxic oxygen metabolites.

Abstract: A B S T R A C T Intravascular activation of the complement system with cobra venom factor results in acute lung injury, which has been quantitated by increases in lung vascular permeability. Cobra venom factor preparations devoid of phospholipase A2 activity retain full lung-damaging capacity. The lung injury is associated with the preceding appearance of chemotactic activity in the serum coincident with the development of a profound neutropenia. The chemotactic activity is immunochemically related to human C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
1
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(202 citation statements)
references
References 18 publications
10
189
1
2
Order By: Relevance
“…Thus, we cannot rule out completely the possibility that C3a and C5a could participate in this model. It has been reported that complement mediated increases in microvascular permeability is entirely dependent on PMNs (Till et al 1982). However, our results in this study suggest that latex microbeads infusion increases permeability independently of PMNs.…”
Section: Discussioncontrasting
confidence: 81%
“…Thus, we cannot rule out completely the possibility that C3a and C5a could participate in this model. It has been reported that complement mediated increases in microvascular permeability is entirely dependent on PMNs (Till et al 1982). However, our results in this study suggest that latex microbeads infusion increases permeability independently of PMNs.…”
Section: Discussioncontrasting
confidence: 81%
“…Attenuation of neutrophil accumulation in the lungs, by using molecules inhibiting neutrophil adhesion, decreased the severity of lung injury (37). In addition, data from animal studies indicate that neutrophil depletion markedly attenuates the severity of endotoxemia-induced ALI (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…These oxygen radicals have been shown to be injurious to cells and tissues [10,11]. In addition O 2~ is able to react with plasma and generate a chemotactic factor for neutrophils, thus amplifying the inflammatory response [12].…”
Section: Introductionmentioning
confidence: 99%